Analisis Permasalahan Perubahan Kurikulum Pada Guru Kelas IV Di SD Negeri 106163 Bandar Kalippa - Demmina Ginting; Lasrumata Ida Nababan; Nurhayati Nurhayati; Romaito B. Pardede; Khairunnisa Khairunnisa (Departement of Mathematics Education, 2024)
The curriculum often changes because the world continues to change and education must adapt to the times. The curriculum must be appropriate to the times and the context and characteristics of students. In facing curriculum changes, teachers experience difficulties in adapting to curriculum changes. This research aims to determine teachers' difficulties in adapting to curriculum changes. The research method used in this research is qualitative research. The data collection technique in the research that we conducted was using face-to-face questions and answers or directly to the subject, then the researcher asked questions by asking the research subject, namely a class IV teacher at SDN No. 106163 Bandar Klippa Percut Sei Tuan named Mrs. Atikah Riqka. , S.Pd. related to educational problems at the school. Teachers' difficulties in adapting technology when teachers have to redesign their learning plans and adapt their learning according to new provisions.